1995
DOI: 10.1007/bf02049735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short chain fatty acids on mucosal proliferation and inflammation of ileal pouches in patients with ulcerative colitis and familial polyposis

Abstract: SCFA do not control inflammation and clinical functions but reduce cell proliferation in UC patients. On the contrary, FAP patients are refractory to SCFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…: POUCHITIS AFTER ILEAL POUCH-ANAL ANASTOMOSIS Various potential factors have been investigated to identify the etiology of CP, including bacterial overgrowth, mucosal atrophy and breakdown resulting from pouch ischemia, and pouchitis as a recurrence of UC. 9,[13][14][15][16] In our study, postoperative complications, specifically anastomotic complications, were associated with the development of pouchitis. This, in combination with the trend toward the decreased development of CP in patients not undergoing a diverting ileostomy, may indicate that the loss of gut integrity is important in the development of CP.…”
Section: Discussionmentioning
confidence: 89%
“…: POUCHITIS AFTER ILEAL POUCH-ANAL ANASTOMOSIS Various potential factors have been investigated to identify the etiology of CP, including bacterial overgrowth, mucosal atrophy and breakdown resulting from pouch ischemia, and pouchitis as a recurrence of UC. 9,[13][14][15][16] In our study, postoperative complications, specifically anastomotic complications, were associated with the development of pouchitis. This, in combination with the trend toward the decreased development of CP in patients not undergoing a diverting ileostomy, may indicate that the loss of gut integrity is important in the development of CP.…”
Section: Discussionmentioning
confidence: 89%
“…NaBu is emerging as an anti-inflammatory drug against ulcerative colitis (Breuer et al, 1991;Scheppach et al, 1992;Tonelli et al, 1995;Steinhart et al, 1996Steinhart et al, , 1994Vernia et al, 2003), diversion colitis (Harig et al, 1989), radiation proctitis (Vernia et al, 2000), pouchitis (Sandborn et al, 2006), and Crohn's disease (Di Sabatino et al, 2005). Our results suggest that NaBu is not able to counteract the effects of cytokines if the cells are already "bathed" with cytokines, implying that to prevent/cure inflammation, NaBu treatment should be started at a very early stage in the inflammatory process.…”
Section: Il-1␤ and Tnf-␣ Inhibit Iap Expression 691mentioning
confidence: 98%
“…Human studies analysing the effects of SCFAs were performed in patients with colonic inflammation using rectal enemas containing SCFA mixtures or butyrate alone (Table 1). 45, 46, 73, 96, 113–126 …”
Section: Butyrate and Inflammationmentioning
confidence: 99%
“…The effects of butyrate containing enemas on radiation proctitis 113, 117, 122, 125 and pouchitis 123 have been studied in small groups and besides one report 125 that showed that butyrate was an effective treatment of radiation proctitis, other studies did not report clear‐cut beneficial effects of SCFA irrigation in these two patient groups 113, 117, 122, 123 …”
Section: Butyrate and Inflammationmentioning
confidence: 99%